Integrative Healing: Exploring the Pharmacological Approach and Impact of Yoga on Depression Following Traumatic Brain Injury - Bajaj, Khushi; Kaur, Navneet; Grewal, Pakhee; Kumar, Hardik (Current Indian Science, 2025)
Traumatic Brain Injury (TBI) is a complex type of brain damage caused by external factors. Depression is one of the major comorbidities that follow, making things more difficult for patients and caregivers. Post-traumatic depression is a serious condition that can increase rates of death and morbidity, especially as it gets worse. Though constant discussion exists about the best ways to treat the condition, a conclusive answer is still out of reach. Interestingly, traditional non-pharmacological treatments that have been used for a long time to treat a wide range of illnesses have just returned to prominence because they may be able to help prevent, treat, and even cure several mental conditions. Among these, yoga stands out as a particularly effective means of enhancing focus, which in turn supports mental health, productivity, and general well-being while reducing thoughts of suicide. Moreover, the technique exhibits a noticeable impact on the control of neurohumoral transmissions, which presents a possible treatment option for post-traumatic depression. This study explores in great detail the complex pathological relationship between traumatic brain injury and depression indicators, highlighting the critical role that yoga plays in the treatment of post-traumatic depression.
Keywords: Cerebral oscillations